Drain placement can safely be omitted for open partial nephrectomy: results from a prospective randomized trial - Kriegmair, Maximilian; Dönmez, Hasan; Häcker, Axel; Michel, Maurice Stephan (International journal of urology, 2016)
Objectives To examine the benefit of drain placement during open partial nephrectomy. Methods Overall, 106 patients treated with open partial nephrectomy were enrolled in a prospective randomized trial. Based on the randomization, a drain was placed or omitted. Complications were assessed according to the Clavien classification. Pain level and requirement for analgesics was evaluated according to a customized pattern. Results There was no significant difference in the two groups regarding age, body mass index, American Society of Anesthesiologists score, tumor size and nephrometry (preoperative aspects and dimensions used for an anatomical classification). In terms of overall and drain-related complications, no advantage of placing a drain could be proven (P = 0.249). Patients with a drain suffered from a significantly higher pain level (P = 0.01) and showed prolonged mobilization (P < 0.001). There was no difference in bowel movements and requirement of additional analgesics (P = 0.347 and 0.11). Conclusions The results of the study suggest that drain placement during open partial nephrectomy can safely be omitted, even in cases with violation of the collecting system.
Gesehen am 08.05.2019